SUBCHRONIC ORAL TOXICITY TEST FOR 28 DAYS OF SAUROPUS ANDROGYNOUS L. MERR. LEAVES SOUP IN WISTAR FEMALE RATS - AGUSLINA KIRTISHANTI; RIDHO ISLAMIE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to evaluate the subchronic toxicity of Sauropus androgynus L. Merr. leaves soup. Methods: Subchronic oral toxicity tests were carried out for 28 days in female Wistar rats using conventional methods. Thirty rats were divided into six groups, namely, one control group and three test groups with each extract being given at a dose of 500 mg/kg body weight (BW), 1000 mg/kg BW, and 3000 mg/kg BW, and one group satellite control and satellite test group with doses of 3000 mg/kg BW were carried out for 14 days after 28 days of treatment to see the effects of reversibility. All rat groups were observed for behavior, development of BW, serum glutamic pyruvic transaminase (SGPT), serum glutamic oxaloacetic transaminase (SGOT), creatinine serum, ratio of liver and lung organs to BW, and histology of liver and lung. Results: The macroscopic observation of rat’s lung and rat weight ratio did not show a significant difference to the control group (p>0.05). In addition, the ratio of liver volume to BW was significantly different between the doses of 1000 mg/kg BW and 3000 mg/kg BW with satellite groups 3000 mg/kg BW (p<0.05). Levels of SGOT and SGPT as well as liver and lung histopathology scores did not show a significant difference to the control group (p>0.05). However, creatinine serum had the highest increase at a dose of 500 mg/kg BW and a dose of 1000 mg/kg BW. Reversibility effects were not seen after 14 days of the past day given Sauropus androgynous soup for 28 days in female Wistar rats. Conclusion: The given of S. androgynous soup for 28 days for female Wistar rats did not show any specific toxicity effect so that its use was relatively safe for the consumption under 30 days. This study is expected to be the information source about the safety profile of S. androgynus leaves soup consumption.